Lithium interaction with polyaromatic hydrocarbons and properties of lithium solvated electron solutions - Liu, Zhihao (Nanyang Technological University, 2019)
Lithium batteries have been wildly used in handheld consumer devices and electric vehicles for their high energy density and portability. They also produce relatively less pollution compared with traditional batteries. To improve their performance, a lot of attentions have been paid to the fundamental level of lithium batteries, especially the properties of anode materials. Current anode materials include solid-state and semi-solid state materials like graphite, carbonaceous materials and alkali metals. However, these materials either have safety problem or have slow recharge rate. In addition, performance of batteries based on these materials is reaching a limit. Recently, researcher has found that lithium solvated solutions (LISES) based on polyaromatic hydrocarbons (PAH) could be achieved by adding metallic lithium to tetrahydrofuran (THF) solution of PAH. These solutions have been proved to have potential application in rechargeable lithium batteries for their low cost, fast recharge rate and good safety. We modeled the interactions between lithium atoms and PAH molecules in the solutions using density functional density theory (DFT) and studied the properties of LISES based on various PAH species. The interaction of lithium atoms with anthracene, p-terphenyl and triphenylene monomers is correlated with the open circuit voltage (OCV) and conductivity of the solutions. Interactions between lithium atoms and anthracene, p-terphenyl and triphenylene clusters were studied to predict the behavior of the systems when depositing lithium into corresponding solids and highly concentrated LISES. The interactions between lithium atoms and nitrogen substituted biphenyl, naphthalene, anthracene were studied to understand the effect of nitrogen in the PAH on the properties of corresponding LISES. The investigation shows LISES could be a good anode material for lithium batteries by increasing lithium loading and reducing electron affinity of the PAH and molecular modeling could be a powerful tool to find better PAH alternatives.